(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
In the Malaysian political landscape, Parti Islam Se-Malaysia (PAS) has grown from a small to an influential Malay-Islamic party under the leadership of three early figures, namely Ahmad Fuad, Abbas Alias and Burhanuddin al-Helmy. Their leadership was essential as they guided the party from its formation to eventually governing states in Malaysia. This study explored the impact of these figures’ leadership on the party and the country over their 18-year tenure. A case study research design was employed to elucidate their leadership experiences. Document analysis was employed to gather data from secondary sources, and thematic analysis was conducted to identify the contributions and challenges faced by these leaders, as well as to assess their leadership efficacy. The results were reported in chronological order, consistent with the historical descriptive analysis employed. The study findings revealed that these political figures had made various contributions, particularly in establishing Islamic ideologies and practices, which paved the way for the party’s direction and fostered electoral success. Despite facing various challenges, PAS has emerged as a party that represents conservative Islam, from right-wing to left-wing nationalism, which later became its core ideology (conservative nationalism) that remains to this day.